A new species of minute beetle (Coleoptera: Clambidae) from Baltic amber (Paleogene, Eocene) - Alekseev, Vitalii I. (Zootaxa, 2017)
A new species of Clambidae, Clambus helheimricus sp. nov., is described and illustrated from Baltic amber. A list of the smallest beetles described from this Lagerstätte is provided.